2020
DOI: 10.3390/antiox9080723
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting Cisplatin-Induced Testicular Damages by Natural Polyphenol Constituent Honokiol

Abstract: Cisplatin, despite its anti-cancer ability, exhibits severe testicular toxicities when applied systemically. Due to its wide application in cancer treatment, reduction of its damages to normal tissue is an imminent clinical need. Here we evaluated the effects of honokiol, a natural lipophilic polyphenol compound, on cisplatin-induced testicular injury. We showed in-vitro and in-vivo that nanosome-encapsulated honokiol attenuated cisplatin-induced DNA oxidative stress by suppressing intracellular reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 54 publications
(83 reference statements)
1
12
0
Order By: Relevance
“…Several studies found that CIS causes severe testicular damage through impairment of Leydig cell function (inhibiting testosterone production) and induction of germ cell apoptosis. Besides the DNA damage, excessive production of reactive oxygen species (ROS) is also implicated as one of the main causes of CIS-induced testicular damage [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that CIS causes severe testicular damage through impairment of Leydig cell function (inhibiting testosterone production) and induction of germ cell apoptosis. Besides the DNA damage, excessive production of reactive oxygen species (ROS) is also implicated as one of the main causes of CIS-induced testicular damage [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Afsar et al methods were used to assess SOD and GPx activity [ 39 , 40 ]. The total antioxidant capacity of testicular tissues was analyzed by OxiSelect Total Antioxidant Capacity Assay (TAC assay, Cell Biolabs, Inc., San Diego, CA, USA) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…CDDP can induce Leydig cell dysfunction and testicular steroidogenic synthesis disorders in animals, inhibiting testosterone production and causing infertility [ 15 ]. Furthermore, CDDP decreases sperm motility and activation [ 16 , 17 ]. CatSper is a voltage-gated calcium channel that is expressed in sperm, and it leads to hyperactivated motility and fertility in males.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin (CIS) is an effective chemotherapy drug for the treatment of testicular cancer, gynecologic cancer, gastrointestinal cancer, and malignant diseases (Albany et al., 2021). However, there are numerous side‐effects during CIS treatment (Azarbarz et al., 2020), especially testicular toxicity (Wang, Lai, et al, 2020). Exposure to CIS led to testicular atrophy and decrease in the number, viability, and motility of sperm, resulting in spermatogenesis inhibition and infertility (Fouad et al., 2017).…”
Section: Introductionmentioning
confidence: 99%